Geopolitical Economy : The South Korean FTA Strategy - Krieckhaus, Jonathan Tabor, 1967- (Book collections on Project MUSE., 2018)
Geopolitical Economy examines the significance and nature of free trade agreements (FTAs), the primary policy tool through which modern nations seek access to international markets and promote economic growth. The book focuses specifically on how South Korea, the world's leader in the number and significance of FTAs as well as the world's sixth largest export economy, uses FTAs. Jonathan Krieckhaus argues that geopolitics-the struggle between powerful nations over specific geographic regions around the globe-influenced FTA strategy and economic policy in South Korea and beyond. This perspective illustrates the security approach to FTAs, but adds that the geographic specificity of security concerns deeply shape FTA policy. Geopolitical Economy also looks at Korean FTAs through the lens of development strategy. South Korea is singularly successful in garnering FTAs with all three players in the global economy: the United States, the European Union, and China. This unprecedented success was built on a strong commitment from three consecutive Korean presidential administrations, each operating within a favorable state-society context that enjoyed the existence of a centralized and effective trade bureaucracy.